2017
DOI: 10.1042/bsr20160603
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of TGF-β/miR-155/c-Ski regulates endothelial–mesenchymal transition in human coronary artery endothelial cells

Abstract: Human coronary artery endothelial cells (HCAECs) have the potential to undergo fibrogenic endothelial–mesenchymal transition (EndMT), which results in matrix-producing fibroblasts and thereby contributes to the pathogenesis of cardiac fibrosis. Recently, the profibrotic cytokine transforming growth factor-β (TGF-β) is shown to be the crucial pathogenic driver which has been verified to induce EndMT. C-Ski is an important regulator of TGF-β signaling. However, the detailed role of c-Ski and the molecular mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…In addition, previous studies have reported that low TGF-β1 concentrations promote the proliferation of muscle, bone (or chondrocytes) and endothelial cells [4,17]. In addition, c-Ski can promote muscle proliferation [18] and participates in endothelial, chondrocyte proliferation [19,20]; c-Ski knockout mice and c-Ski-deficient individuals have defective bone and muscle development [21]. Therefore, these results indicate that proliferation of these cells induced by low TGF-β1 concentrations may also be mediated through the induction of c-Ski.…”
Section: Low Tgf-β1 Concentrations Promote Skin Fibroblast Proliferatmentioning
confidence: 98%
“…In addition, previous studies have reported that low TGF-β1 concentrations promote the proliferation of muscle, bone (or chondrocytes) and endothelial cells [4,17]. In addition, c-Ski can promote muscle proliferation [18] and participates in endothelial, chondrocyte proliferation [19,20]; c-Ski knockout mice and c-Ski-deficient individuals have defective bone and muscle development [21]. Therefore, these results indicate that proliferation of these cells induced by low TGF-β1 concentrations may also be mediated through the induction of c-Ski.…”
Section: Low Tgf-β1 Concentrations Promote Skin Fibroblast Proliferatmentioning
confidence: 98%
“…Importantly, Ski overexpression inhibits the TGF-β-induced EndMT of HCAECs via a mechanism that involves the regulation of miR-155. 107 During liver fibrogenesis induced by TGF-β and acetaldehyde, an ethanol metabolite, increased collagen synthesis occurs in hepatic stellate cells (HSC); in these cells, the Ski/Smad4 complex is translocated to the cytoplasm, and the Ski protein is degraded via UPS. 244 In systemic sclerosis, the levels of the Ski and SnoN proteins are increased in scleroderma fibroblasts, although they fail to inhibit the TGF-β pathway because they are unable to compete with the p300 coactivator.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
“…15,16 Thus, understanding the pathogenesis of cardiac fibrosis may identify promising targets for the treatment of patients with AF. 20 Zhang et al found that c-Ski can ameliorate isoproterenol-induced myocardial fibrosis in a rat model and reduce both TGF-β1-induced proliferation of primary rat cardiac fibroblasts and ECM deposition. [17][18][19] Recently, researchers have focused on the effects of c-Ski in cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also suggest that the c-Ski protein plays an important role in the development of nerve and muscle as well as in organ fibrosis. [17][18][19] Recently, researchers have focused on the ef- 20 Zhang et al found that c-Ski can ameliorate isoproterenol-induced myocardial fibrosis in a rat model and reduce both TGF-β1-induced proliferation of primary rat cardiac fibroblasts and ECM deposition. 19 Our team previously determined the involvement of c-Ski in the regulation of TGF-β-induced proliferation of human cardiac fibroblasts and ECM protein expression.…”
Section: Discussionmentioning
confidence: 99%